Mucous cell distribution and mucus production during early growth periods of the giant African snail (Achatina fulica) - Suwannapan, Wipawadee; Ngankoh, Supawadee; E-kobon, Teerasak; Chumnanpuen, Pramote (Agriculture and Natural Resources, 2019)
The giant African snail (Achatina fulica) secretes mucus for crawling and protection from moisture loss and pathogenic infections. The snail mucus has been popularly used as a bioactive reagent in medical and cosmeceutical products. This study observed the distribution of pedal mucous cells of A. fulica and the snail growth effect (1–3 mth) on pedal mucus production and the types of mucous cells. Foot tissues were processed using a paraffin technique and stained with Masson’s trichrome, periodic acid Schiff, and periodic acid Schiff-Alcian Blue at pH 2.5. Visualization under a light microscope showed that the pedal mucus of A. fulica was mainly produced from two types of mucous glands: 1) tubular mucous gland cells located on the dorsal part of foot that produced acid mucopolysaccharide mucus; and 2) round mucous gland cells located on the ventral part of foot that produced acid and neutral mucopolysaccharide mucus. A positive correlation between the acid mucin level and snail age was only observed on the dorsal area. The level of neutral mucin from both sides was highest after 2 mth. The average length of the mucous cells on the dorsal surface significantly increased during growth. This study revealed the change and distribution of the mucous cells in early A. fulica development to inform further applications in snail bioactive compounds.